PHASE IDENTIFICATION IN THE TL2O3-BAO SYSTEM - BA2TL2O5 AND BA4TL6O13 - Zhou, W; Liu, R; Edwards, P (1990)
Ba2Tl2O5 has been reinvestigated by a combination of X-ray diffraction, electron diffraction, and energy dispersive X-ray spectroscopy. A new monoclinic unit cell was observed with a = 5.836, b = 6.226, c = 17.342 Å, and γ = 91.34°. The impurity phase coexisting with Ba2Tl2O5 was determined to be Ba4Tl6O13, having an orthorhombic unit cell with a = 5.748, b = 7.221, and c = 9.361 Å. The possible mechanism of solid-solid reaction of Ba, Tl oxides is discussed. © 1990.